Vagus Nerve Stimulation for Depression: A Systematic Review - Lv, Hang; Zhao, Yan-hua; Chen, Jian-guo; Wang, Dong-yan; Chen, Hao (Frontiers in Psychology, 2019)
Background: Depression is a common mental disorder worldwide, psychological treatments and antidepressant medication are the usual treatment for depression. However, there is a large proportion of patients with depression who still do not respond to the currently available treatments.Vagus nerve stimulation(VNS) may be an option for the adjunctive long term treatment of chronic or recurrent depression. But there is still no sufficient evidence of VNS for treating depression. Accordingly, we performed a systematic review for to evaluate the efficacy and safety of VNS. Methods: We conducted a systematic review in accordance with the Cochrane Handbook for Systematic Reviews of Interventions. Systematic search was performed in the database of Pubmed, Embase, CENTRAL and Web of science for identifying the suitable trials. Suicidal rate was considered as the primary outcome in this review. Meta-analysis was performed in the case of enough trials with homogeneity were included. Result: Only two randomized sham controlled add-on studies involved 255 (134 in VNS group and 121 in control) patients were included in this review. None of the studies reported suicidal rate. We performed a qualitative analysis and it is suggested that there was no significant statistic difference between VNS and sham VNS on the score change of 24-item Hamilton Rating Scale for Depression (HAMD24) (MD: -2.40, 95% CI: -7.90 to 3.10). Similar findings were also reported on improvement percentage of HAMD24 (MD:1.00, 95%CI: -6.06 to 8.06); Montgomery-Asberg Depression Rating Scale (MADRS) (MD: 4.70, 95%CI: -2.98 to 12.38) and 30 item Inventory of Depressive Symptomalogy-Self-Report (IDS-SR30) (MD: 4.9, 95%CI: -1.89 to 11.69). While for Beck Depression Inventory self-rating score, there was a margin of statistical significance between the real and sham treatment (MD: 7.80, 95%CI: 0.34 to 15.26). A minor effect of IDS-SR30 was also found in real VNS group (RR: 2.33, 95% CI: 1.07 to 5.10). Conclusion: The efficacy and safety of VNS for depression is still unclear, there is no sufficient evidence for VNS in treating depression, further randomized controlled trials, especially focus on suicide rate are still needed.